ANALISIS KANDUNGAN ASAM ASKORBAT DALAM BUAH NAGA MERAH (Hylocereus polyrhizus) DENGAN IODIMETRI - Abdul Rahim; Alimuddin Alimuddin; Erwin erwin (JURNAL KIMIA MULAWARMAN, 2016)
ABSTRACT             The research to determine “Analysis the Content of Ascorbic Acid in the Red Dragon Fruit by Iodimetri” Vitamin C concentration of postharvest red dragon fruit (Hylocereus Polyrhizus) and at the same time to recognize those the packaging could affected conten of obtained Vitamin C. Analysis process was conducted by iodimetric titration method through the sample of dragon fruit with saving period and packaging varied. The result of completed research find out there was are difference concentration of Vitamin C between packaged dragon fruit and without package, the concentration of Vitamin C in packaged dragon fruit was increase the concentration of Vitamin C from the first day (11,1680 mg/100 gram of sample) to the third day (14,8017 mg/100 gram of sample) and decrease until the fifth day (10,4743 mg/gram of sample), otherwise by another treatment without package the concentration of Vitamin C are increase from the first day (7,4928 mg/100 gram of sample) to the sixth day (19,6784 mg/100 gram of sample) and decreased until the eighth day (14,1395 mg/100 gram of sample). Keywords  : Red dragon fruit (Hylocereus Polyrhizus), Vitamin C dan iodimetric titration.